2004
DOI: 10.1038/sj.eye.6700521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome following cataract surgery in very elderly patients

Abstract: Surgeons should not be deterred from offering cataract surgery to the very elderly as successful visual rehabilitation is the norm. A further prospective multicentre study is required to confirm the benefits and assess the risks of cataract surgery in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
3

Year Published

2005
2005
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
3
29
0
3
Order By: Relevance
“…Cataract surgery is one of the most common and safe surgical procedures worldwide [1]. Phacoemulsification and recent advances in cataract surgery techniques led to improved postoperative outcomes [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataract surgery is one of the most common and safe surgical procedures worldwide [1]. Phacoemulsification and recent advances in cataract surgery techniques led to improved postoperative outcomes [1].…”
Section: Introductionmentioning
confidence: 99%
“…Phacoemulsification and recent advances in cataract surgery techniques led to improved postoperative outcomes [1]. Nowadays, along with the improvement in biometry and corneal topography in preoperative examination, patients presenting with cataract can be diagnosed with corneal ectasias, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although cataract surgery is the most effective, common, and safe ophthalmic procedure to treat cataract, [1][2][3] the complications of cataract surgery may result in blindness and thus ruin the patient's quality of life. For the safety of patients, it is very important to monitor and improve the quality of cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4,12 In the present study, only a few patients (6%) did not have expected VA levels because of posterior capsule perforation, postoperative cystoid macular edema and corneal stromal edema. Syam and colleagues 13 reported that surgeons should not be deterred from offering cataract surgery to the very elderly, as successful visual rehabilitation is the norm. Nonetheless, they suggest that a further prospective multicentre study is required to confirm the benefits and to assess the risks of cataract surgery in this age group.…”
Section: Discussionmentioning
confidence: 99%